Long-term detection of seasonal influenza RNA in faeces and intestine. (September 2016) - Hirose, R.; Daidoji, T.; Naito, Y.; Watanabe, Y.; Arai, Y.; Oda, T.; Konishi, H.; Yamawaki, M.; Itoh, Y.; Nakaya, T.
Abstract: Some cases of seasonal influenza virus (human influenza A virus (IAV)/human influenza B virus (IBV)) are associated with abdominal symptoms. Although virus RNA has been detected in faeces, intestinal infection has not been clearly demonstrated. We aimed to provide evidence that IAV/IBV infects the human intestine. This prospective observational study measured virus RNA in faecal and sputum samples from 22 patients infected with IAV/IBV (19 IAV positive and three IBV positive). Nineteen patients were included in the analysis and were assigned to faecal IAV-positive and -negative groups. Virus kinetics were examined in faecal samples from an IAV-infected patient (patient 1) and an IBV-infected patient (patient 2). Finally, intestinal tissue from an IAV-diagnosed patient who developed haemorrhagic colitis and underwent colonoscopy was examined for the presence of replicating IAV (patient 3). Virus RNA was detected in faecal samples from 8/22 IAV/IBV-infected patients (36.4%). Diarrhoea occurred significantly more often in the faecal IAV-positive group (p 0.002). In patients 1 and 2, virus RNA became undetectable in sputum on days 7 and 10 after infection, respectively, but was detected in faeces for a further 2 weeks. Virus mRNA and antigens were detected in intestinal tissues (mucosal epithelium of the sigmoid colon) from patient 3. These findings suggest that IAV/IBV infects within the intestinal tract; thus, the human intestine may be an additional target organ for IAV/IBV infection.